TNF-α mutation affects the gene expression profiles of patients with multiple trauma. (August 2015) - Chen, GT; Han, N; Li, GF; Li, X; Li, G; Liu, YZ; Wu, W; Wang, Y; Chen, YX; Sun, GX; Li, ZC; Li, QC
Multiple trauma can induce sepsis and organ failure, even threaten people's lives. To further study the mechanisms of multiple trauma, we analyzed microarray of GSE5760. GSE5760 was downloaded from the Gene Expression Omnibus including a total of 58 peripheral blood transcriptome from patients without (WT, n = 30) and carrying (MUT, n = 28) the tumor necrosis factor (TNF) rs1800629 A variant. The differentially expressed genes (DEGs) were screened using the limma package in R and the Benjamin and Hochberg method in a multi-test package. Then, functional enrichment analysis of DEGs was performed. Also, transcription factors significantly related to DEGs were searched using WebGestalt and interaction network of transcription factors and DEGs were constructed using STRING online software. Furthermore, pathway enrichment analysis for the DEGs in the interaction network was conducted using KO-Based Annotation System (KOBAS). We screened 39 DEGs including 27 upregulated and 12 downregulated genes. The enriched functions were associated with biological process (BP) (such as response to hypoxia, P value = 0.039803), cell components (CC) (such as mitochondrial part, P value = 0.043857), and molecular function (MF) (such as structural constituent of ribosome, P value = 0.008735). Besides, RPS7 and RPL17 were associated with ribosome and participated in ribosome pathway. PPP2R2B was related to mitochondrion. KCNMA1, ALAS2 and SOCS3 were associated with hypoxia. Moreover, transcription factors of LEF1, CHX10, ELK1, SP1, and MAZ were significantly related to DEGs. RPS7, RPL17, PPP2R2B, KCNMA1, ALAS2, and SOCS3 might relate to multiple trauma. And TNF-α mutation could cause sepsis in patients with multiple trauma by changing the expression of these genes.